Different degree of loss‐of‐function among four missense mutations in the EDAR gene responsible for autosomal recessive hypohidrotic ectodermal dysplasia may be associated with the phenotypic severity. Issue 3 (18th October 2022) - Yagi, Sasagu; Yasuno, Shuichiro; Ansai, Osamu; Hayashi, Ryota; Shimomura, Yutaka
Abstract: Hypohidrotic ectodermal dysplasia is a rare condition characterized by hypohidrosis, hypodontia, and hypotrichosis. The disease can show X‐linked recessive, autosomal dominant or autosomal recessive inheritance trait. Of these, the autosomal forms are caused by mutations in either EDAR or EDARADD . To date, the underlying pathomechanisms or genotype–phenotype correlations for autosomal forms have not completely been disclosed. In this study, we performed a series of in vitro studies for four missense mutations in the death domain of EDAR protein: p.R358Q, p.G382S, p.I388T, and p.T403M. The results revealed that p.R358Q‐ and p.T403M‐mutant EDAR showed different expression patterns from wild‐type EDAR in both western blots and immunostainings. NF‐κB reporter assays demonstrated that all the mutant EDAR showed reduced activation of NF‐κB, but the reduction by p.G382S‐ and p.I388T‐mutant EDAR was moderate. Co‐immunoprecipitation assays showed that p.R358Q‐ and p.T403M‐mutant EDAR did not bind with EDARADD at all, whereas p.G382S‐ and p.I388T‐mutant EDAR maintained the affinity to some extent. Furthermore, we demonstrated that all the mutant EDAR proteins analyzed aberrantly bound with TRAF6. Sum of the data suggest that the degree of loss‐of‐function is different among the mutant EDAR proteins, which may be associated with the severity of the disease.